2021
DOI: 10.1186/s13568-021-01267-9
|View full text |Cite
|
Sign up to set email alerts
|

A case–control study on the association of intestinal flora with ulcerative colitis

Abstract: The association between intestinal flora and ulcerative colitis (UC) was studied in order to provide a basis and method for clinical treatment. Fresh fecal samples were collected from 30 active UC patients and 10 healthy controls. The intestinal flora DNA from each sample was extracted and 16S rRNA gene sequencing was carried out using HiSeq platform to identify the intestinal flora in fecal samples. The richness and diversity of intestinal flora in UC patients were significantly lower than those in healthy co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 26 publications
(28 reference statements)
1
12
0
Order By: Relevance
“…In the responsive group, the decreased enterobacteria, which is generally considered to play a pro-inflammatory role in UC, is the most likely cause of inflammation reduction. As expected, the previously reported altered taxa associated with UC were also found in our study, including the enrichment of Proteobacteria, Enterococcus, and Turicibacter, and also the lack of Anaerostipes, Coprococcus, Roseburia, Faecalibacterium, Ruminococcus, and Gemmiger ( Tang et al, 2021 ; Volkova and Ruggles, 2021 ; Xu et al, 2021 ; Zhuang et al, 2021 ). There was no differential taxa observed in the nonresponsive group at week 6 and we speculated this might be attributed to the slight change and small sample size.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the responsive group, the decreased enterobacteria, which is generally considered to play a pro-inflammatory role in UC, is the most likely cause of inflammation reduction. As expected, the previously reported altered taxa associated with UC were also found in our study, including the enrichment of Proteobacteria, Enterococcus, and Turicibacter, and also the lack of Anaerostipes, Coprococcus, Roseburia, Faecalibacterium, Ruminococcus, and Gemmiger ( Tang et al, 2021 ; Volkova and Ruggles, 2021 ; Xu et al, 2021 ; Zhuang et al, 2021 ). There was no differential taxa observed in the nonresponsive group at week 6 and we speculated this might be attributed to the slight change and small sample size.…”
Section: Discussionsupporting
confidence: 91%
“…High taxonomic and metabolic observed OTUs and Shannon index seemed to be positively associated with more severe inflammation (high full Mayo score and pro-inflammatory cytokines levels), despite that CRP negatively correlated with the Shannon index. The genera which have significant coefficients with clinical biomarkers are the most pro-inflammatory genus and have been reported to be linked with UC previously ( Tang et al, 2021 ; Xu et al, 2021 ; Zhuang et al, 2021 ). Collinsella has been reported to efficiently colonize in the solid mucin-agar part of mucosal surfaces and belong to pro-inflammatory bacteria ( Astbury et al, 2020 ; van Soest et al, 2020 ).…”
Section: Discussionmentioning
confidence: 95%
“…In this regard, we first tested whether consumption of NEPs versus EPs and DFs could differentially regulate the composition of gut microbiota in UC mice. It was found that ingestion of NEPs significantly increased the abundance of Muribaculaceae, Ileibacterium, Alloprevotella, Lactobacillus, and Alistipes and remarkably decreased the abundance of Lachnospiraceae, and these bacteria have been previously reported to be associated with the regulation on UC. It is worth noting that NEPs were more effective than EPs or DFs in restoring gut microbiota dysbiosis (Figure ). In addition, Muribaculaceae and Lactobacillus were demonstrated to be potentially beneficial for relieving inflammation and facilitating immunocompetence in colitis mice .…”
Section: Discussionmentioning
confidence: 75%
“…In addition to the well-known oxidative stress, gut microbiota is also thought as another factor affecting the progression of UC. 47 Recent literatures suggested that C 60 (or derivatives) might change the gut flora structure, [26][27][28] but in-depth discussion regarding the relationship between microbiota alternation and UC symptoms is lacking. For this purpose, the 16S rRNA gene sequencing method was first applied to investigate the possible change of intestinal flora composition that resulted from the treatment of RL/C 60 .…”
Section: Modulation Effect Of Rl/c 60 On the Composition Of Intestina...mentioning
confidence: 99%